Redi award lecture: Clinical studies of snake-bite in four tropical continents - Warrell, D (2013)
Research is discussed in the areas of venomous snake taxonomy, epidemiology, species diagnosis, defining the clinical phenotype of human envenoming, pathophysiological mechanisms of envenoming, clinical testing of antivenoms and prevention of snake-bite through community education. This work was carried out over the past 40 years in many countries in four tropical continents. The help and friendship of a large number of collaborators is gratefully acknowledged. © 2012 Elsevier Ltd.